2023
DOI: 10.4018/978-1-6684-6386-4.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Classroom

Abstract: In early years settings and schools, the population of children from diverse ethnic backgrounds has been increasing all over the world. Along with this increase, there is growing interest and concern in meeting the needs of these children and their families throughout their early years and school experience. Within any mainstream culture it is assumed that an ethnically diverse population should be able to be successfully integrated; however, it is not always clear how this could be achieved. Adaptation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Firstly, the findings highlighted that-beyond the MOOC experience-teachers who participated in the study reported scores reflecting a more competent use of all five Conflict Management Styles when compared with the normative group, the latter comprising a sample of general Italian workers employed in public and private organizations (Majer 1995). These data are, however, in line with the ongoing transformations of the educational context; indeed, according to the European agenda, nowadays, teachers are increasingly demanded to promote mutual understanding, respect, and integration among students, rather than reaching high-quality learning outcomes alone (Ası and Joyce 2023;EC 2017EC , 2020. They need to favor a satisfactory class climate, manage relationships with and between students, and deal with the potential conflicts that could occur during classes, also due to the increasing differences in values, worldviews, and cultures in our society (e.g., Jackson and O'Grady 2019;Loode 2011;Meissner et al 2023).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Firstly, the findings highlighted that-beyond the MOOC experience-teachers who participated in the study reported scores reflecting a more competent use of all five Conflict Management Styles when compared with the normative group, the latter comprising a sample of general Italian workers employed in public and private organizations (Majer 1995). These data are, however, in line with the ongoing transformations of the educational context; indeed, according to the European agenda, nowadays, teachers are increasingly demanded to promote mutual understanding, respect, and integration among students, rather than reaching high-quality learning outcomes alone (Ası and Joyce 2023;EC 2017EC , 2020. They need to favor a satisfactory class climate, manage relationships with and between students, and deal with the potential conflicts that could occur during classes, also due to the increasing differences in values, worldviews, and cultures in our society (e.g., Jackson and O'Grady 2019;Loode 2011;Meissner et al 2023).…”
Section: Discussionmentioning
confidence: 97%
“…For this very reason, teachers, globally, are pressured by growing expectations, as they need to possess or acquire new individual and relational skills to successfully fulfill the teaching role (Ası and Joyce 2023;EC 2017;Vallone et al 2022). Specifically, they need to possess/enhance not only their knowledge and awareness about multicultural education but also their individual skills to deal with potential conflicts which could arise in classes due to differences/mismatches in values, cultural backgrounds, and worldviews (Evans et al 2009;Han and Han 2019;Kunemund et al 2020).…”
Section: Introductionmentioning
confidence: 99%